Empress Agnes of Poitou (1043-1077). Reflections on the Legal Basis of Her Regency - Butz, Eva-Maria (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
During the 10th and 11th century Ottonian and Salian queens and empresses became more influential than ever before in the East-Frankish and German Empire. Evidence of female participation in governance is documented by the large number of interventions in royal charters, in addition to the designation of the empress as consors regni, as the co-partner in the reign. However, female rulers were not accepted on an equal footing with male rulers. Agobard of Lyon described already in the 9th century the empress as an essential assistant to the ruler, helping him in ruling and managing the court and empire.. At the beginning of the 11th century, Wipo, a writer at the royal court, denoted queen Gisela as necessaria comes, an indispensable companion of Conrad II. In her role as necessaria comes she was first and foremost the wife who proved to be an eminently efficient counsellor. To her 11th century contemporaries, a queen not only had the right but also the duty to be involved in ruling. However, she could not legally claim her share in power.